Design of electronic multimedia textbook by the order of the armed forces of Ukraine - Biziuk, A.; Zmiivska, N. (Universidad de Guanajuato Primera Edición, 2025)
Based on the analysis of the initial data and the target audience, the infor-mation structure of the electronic publication, which is ordered by the Mili-tary Law Institute of the Yaroslav Mudryi National Law University, has been determined. The necessity and information content of structural elements (modules, screens) have been substantiated.
Keywords: target audience; multimedia